Detection of the BK virus in post-transplant patients in a tertiary care hospital - Choudhary, Vinita; Choudhary, Chetan; Saraswat, Pushpendra (Journal of Applied Pharmaceutical Research, 2023)
Background: Polyomaviruses are small (45 nm) non-enveloped circular double-stranded DNA and belong to the Polyomaviridae family, with Polyomavirus as the only genus. The polyomaviruses are omnipresent. The primary sites of BK virus appearance are the kidney tubular epithelial cells and urinary bladder surface transitional cells. To detect the BK virus in post-transplant patients by molecular methods. Materials and methods: Specimens of 88 patients were collected aseptically in Vials. Nucleic acid was extracted manually and processed in real-time PCR for identification of the BK virus. Result: This study analyzed 88 samples from suspected BK virus patients from January 2022 to January 2023.There were 88 samples tested, 24(27.27%) were positive and 64(72.72%) were negative. Conclusion: The prevalence pattern of BK virus presented in post-transplant patients 24(27.27%) were positive. BKV induces both difficult diagnosis and treatment; transplant recipients are recommended to be under strict surveillance and receive early intervention.